Manajemen National Paralympic Committee Of Indonesia (NPCI) Sulawesi Selatan Dalam Pembinaan Paralympian Di Sulawesi Selatan - Herman, Herman; Himawan, Muhammad; Nawir, Nukhrawi (UNIVERSITAS NEGERI MAKASSSAR, 2020)
ABSTRACTThis research is a descriptive study that aims to determine National Paralympic Committee Of Indonesia Sulawesi South Sulawesi management in building Paralympian in South Sulawesi. The population and samples in this study were all members of a disability sports coaching program. The research subject amounted to 62 people where a manager of 25 trainers was 7 and athletes were 30 people. Data collection techniques using poll. A total of 27 kuisoners of the question consist of 5 answers, namely always, often , sometimes, rarely, never . The collected Data is analysed in a descriptive way and uses the Likert scale. The results of the study have a percentage of each category, namely, the planning is at a strong position of 2045 (78.65%) Of the expected score of 2600 (100%). Organizing is at a strong position of 1547 (79.33) of the expected score of 1950 (100%). The implementation is in a strong position of 1802 (79.20) of the expected score of 2275 (100%). Supervision is at a strong position of 1525 (78.20) of the expected score of 1950 (100%).